Application of modified subtotal resection of adenomyosis combined with LNG-IUS and GnRH-a sequential therapy in severe adenomyosis: A case series - Qin, Zhenyue; Dong, Zhiyong; Tang, Huimin; Zhang, Shoufeng; Wang, Huihui; Bao, Mingyue; Wei, Weiwei; Shi, Ruxia; Chen, Jiming; Xia, Bairong (Frontiers in Surgery, 2022)
Objective:To explore the clinical effect of modified subtotal resection of adenomyosis combined with LNG-IUS and GnRH-a in the treatment of severe adenomyosis, and to determine the feasibility of this scheme. Methods:64 patients with severe adenomyosis in the Department of Gynecology, the Affiliated Changzhou No. 2 People's Hospital of Nanjing Medical University from December 2017 to September 2021 were analyzed retrospectively. The modified subtotal resection of adenomyosis was performed by transabdominal approach / laparoscopic approach / laparoendoscopic single-site approach respectively, and then were divided into transabdominal approach subgroup and endoscopic approach subgroup according to different approaches. Adopting the method of self-control, the hemoglobin, pain score, menstruation score and other indexes were observed and recorded before and after treatment. Results: All the 64 patients completed the operation successfully. After the completion of sequential treatment, the CA125 decreased significantly 1 month postoperative, the average uterine volume was significantly reduced and the hemoglobin value increased to a certain extent 3 months postoperative, and the menstrual score and dysmenorrhea during the first menstruation were significantly lower than before. After completion of treatment, there were no statistical difference between the abdominal and endoscopic subgroup(P＞0.05). Only one patient had downward movement of the IUD, and the vaginal ultrasound showed that the upper end of the IUD was about 1.5cm from the bottom of the uterine cavity. The average follow-up was (24.02 ±11.77)months (5-50 months),No lesion progression was found in the patient.Conclusion: For patients with severe adenomyosis without pregnancy planning and requiring uterine preservation, when the effect of conservative treatment such as drugs is not good. Transabdominal or laparoscopic subtotal resection of the focus of adenomyosis combined with LNG-IUS+GnRH-a sequential treatment may be safe and effective.